Play-within-the-Play between Theatre Anthropology, System Theory and Postcolonial Criticism - Čale-Feldman, Lada (2004)
Taking as its starting point the work on the play within the play procedures in the 20th century Croatian drama, the paper proposes various avenues into the theory of the play within the play procedures, arguing for an approach which would take into account the cultural context of the use of this procedure, seemingly exemplifying the disinterested autoreproduction of the system of drama.